Use of Literacy Tree Rewards in Motivating the Reading of Deaf Students - Kartini, Kartini (Universitas Negeri Makassar, 2022)
Reading is a basic thing that must be mastered by students, because reading is the basis of every science. By reading, it is hoped that deaf students will broaden their horizons and knowledge and increase their vocabulary. It is often found that the problem experienced by deaf students is the lack of motivation to read both at home and at school. This article aims to describe the application of the literacy tree reward media and to find out the effect of the media on the reading motivation of deaf students in class VII at SLB Bekasi Jaya Bekasi City both at home and at school. This study uses a qualitative descriptive approach with observation, interviews and the results of a questionnaire/survey of motivation and interest as well as direct observation and experience. The results of observations, interviews and questionnaires took place before using the literacy tree reward media and after using the literacy tree reward. The results showed that the use of the literacy tree reward can increase reading motivation in class VII deaf children at SLB Negeri Bekasi Jaya, Bekasi City. With the increased motivation to read in deaf children, it is hoped that the habit of playing games during recess is reduced, students are more serious when they get reading assignments and students like to go to the library.